A (Socio)linguistic Approach to Hagiographic Text Transmission: the Torino Collection Biblioteca Nazionale D.v.3. (8th/9th c.) - van Acker, Marieke (Apocrypha, 2012)
Abstract The transmission and reception of hagiographical texts is the central concern of the international research project “An Assessment of Merovingian hagiographical texts in their oldest manuscript versions” directed by Monique Goullet. This project advocates a return to the oldest hagiographical manuscripts in order to free research from the distorting impact of old editions, and to bring it in line with recent scholarly advances in both hagiographical and sociolinguistic studies. A return to the oldest hagiographic manuscripts can, on the one hand, lead to a better understanding of the way in which the first anonymous hagiographic collections were constituted, and, on the other, shed light on the way in which written language functioned in the pre-Carolingian period. It is within this context that the research team chose to edit one of these oldest manuscripts, Torino, Biblioteca Nazionale D.V.3. From a linguistic point of view, this document dating from the end of the 8th or the beginning of the 9th century is a precious witness to the management of written language. It also instructs us on the way its producers handled the inheritance of Latin hagiographical texts written between the 5th and the 8th century. This article takes stock of the linguistic analysis of the collection and of the interpretation of its linguistic features. Abstract La transmission et la réception de textes hagiographiques sont au centre de l’intérêt dans le projet de recherche international “Expertise de textes hagiographiques mérovingiens dans leurs plus anciennes versions manuscrites” dirigé par Monique Goullet. Ce projet prône un retour aux plus anciens manuscrits afin de s’affranchir des éditions anciennes et d’être mieux en phase avec les avancées scientifiques actuelles tant sur le plan des études en hagiographie qu’en sociolinguistique rétrospective. Un retour aux manuscrits hagiographiques les plus anciens permettra de mieux saisir quand et comment se sont constitués les premiers groupements textuels hagiographiques anonymes d’une part, et permettra d’autre part de contribuer à une meilleure compréhension du fonctionnement de la langue écrite à l’époque précarolingienne. C’est dans ce contexte qu’il a été choisi d’éditer l’un de ces manuscrits, le manuscrit Torino, Biblioteca Nazionale D.V.3. Du point de vue linguistique, ce document datant de la fin du viiie ou du début du ixe siècle, est un observatoire intéressant de la gestion de la langue écrite. Un tel légendier nous instruit en effet sur la manière dont ses producteurs géraient un patrimoine de textes hagiographiques latins écrits entre le ve et le viiie siècle. L’article fait le point sur l’analyse linguistique du recueil et sur l’interprétation des traits linguistiques observés.